Stimulus-induced rhythmic, periodic, or ictal discharges (SIRPIDs): an intriguing EEG phenomenon - Mariana Ribeiro Marcondes da Silveira; Joaquina Andrade; Eliana Garzon (Arquivos de Neuro-Psiquiatria)
SIRPIDs, an acronym for stimulus-induced rhythmic, periodic, or ictal discharges, were first named in 2004. This is a pattern observed in continuous electroencephalogram (CEEG) consistently elicited by stimulation in comatose patients. The pathophysiology of SIRPIDs probably involves dysregulation of subcortico–cortical projections, particularly thalamocortical circuit, in a markedly abnormal brain with hyperexcitable cortex. This may explain some studies found an association of prolonged periodic epileptiform discharges (PEDs) activity and a higher incidence of concurrent electrographic seizures and SIRPIDs. An association of SIRPIDs and poor prognosis has already been described. However, it is not yet possible to assert whether these discharges can cause neuronal injury or if they are simply a marker of severe brain injury. Objective of this paper is to review clinical relevance and pathophysiology of SIRPIDs, as well as its role as a brain response in the critically ill patient.